Fjellrev i Finnmark : forskning og tiltak 2004 - Langeland, K.; Ims, Rolf Anker; Killengreen, Siw Turid; Skog, E.; Scheie, J.O.; Yoccoz, Nigel Gilles; Bråthen, Kari Anne (Universitetet i Tromsø, 2004)
Faglig årsrapport for 2004 til DN.